Mapping Social Media Insider Threat Attack Vectors - Armstrong, Colin (IEEE Computer Society, 2013)
Of the many possible insider threat attack vectors the increasing adoption of social media technologies and applications and the changing generational mindset of young prospective employees poses a particular challenge for maintaining security. This paper discusses an approach using network science techniques to map attack vectors and seeing the security problem as either a puzzle to be resolved or a mystery in need of better understanding.